An Assessment of Soil Compaction after Logging Operations in Central Amazonia. Issue 2 (26th November 2019) - DeArmond, Daniel; Ferraz, João B S; Emmert, Fabiano; Lima, Adriano José Nogueira; Higuchi, Niro
Abstract: In the forests of the Amazon Basin, there are still few studies on soil compaction caused by logging activities. This study evaluated an operation located on the property of a timber company in Central Amazonia, which uses harvesting techniques based on the harvesting system developed by the Centre for Agricultural Research in Suriname. The timber-extraction method employed by the timber company consists of three activities: (1) skid trail construction with a track-type tractor, (2) log winching with a winch attached to the tractor, and (3) log skidding with a rubber-tired skidder. Soil bulk density and soil penetration resistance were quantified to 20 cm in depth. After a single tractor ingress and egress for trail construction, the soil incurred an increased root growth-limiting bulk density and penetration resistance. However, log winching did not cause significant soil compaction. The conclusions of the study were: (1) the greatest impact from this harvesting system came from the skid trail construction, (2) the technique of log winching limited forest floor compaction and disturbance that damages forest regeneration, and (3) log skidding during dry soil conditions limited increases in compaction and track formation.